The Effect of Online Learning on The Academic Achievement Among Students of Jordanian Private Universities in Light of The Covid-19 Pandemic, Based on The Variables of Comprehension and Analysis from The Perspective of Faculty Member - Al-Baher, Ibrahim Ali; Flouh, Rawan Fayyad; Al-Sulaihat, Rawan (Technium Social Sciences Journal, 2021)
The current study aimed to identify the impact of online learning on the academic achievement among students of private Jordanian universities in light of the COVID-19 pandemic. The study sample, which was a stratified random sample, consisted of (378) faculty members. Descriptive survey method was used in the current study. In order to achieve the objectives of the study, a questionnaire was developed, and its validity and reliability were verified. The results showed that the effect of online learning on the academic achievement among students of private Jordanian universities in light of the COVID-19 pandemic was average; results of the study also showed statistically significant differences at the significance level (a less or equal 0.05) according to the gender variable in favor of females, and no statistically significant differences according to either the type of college variable, or years of experience’ variables. In light of these results, the study recommended that private Jordanian universities pay great attention to online education, providing it with the appropriate infrastructure, because this may contribute to enriching the cognitive skills received, upgrading students’ behavioral level, and actively contributing to improving students’ academic achievement.